Diagnostic accuracy of pre‐treatment biopsy for grading cutaneous mast cell tumours in dogs. (31st August 2017) - Shaw, T.; Kudnig, S. T.; Firestone, S. M.
Abstract : Mast cell tumours (MCTs) are common tumours of the canine skin, and are estimated to represent up to 20% of all skin tumours in dogs. Tumour grade has a major impact on the incidence of local recurrence and metastatic potential. In addition to helping the clinician with surgical planning, knowledge of the tumour grade also assists in proper prognostication and client education. For pre‐treatment biopsies to be useful, there must exist a high level of correlation between the histopathological grade obtained from the pre‐treatment biopsy and the actual histopathological grade from the excisional biopsy. The aim of this study was to determine concordance of tumour grade between various biopsy techniques (wedge, punch, needle core) and the "gold standard" excisional biopsy method. We found an overall concordance rate of 96% based on the Patnaik grading system, and an overall concordance rate of 92% based on the Kiupel grading system. The accuracy of the various biopsy techniques (wedge, punch and needle core) when compared with excisional biopsy was 92%, 100% and 100%, respectively, based on the Patnaik grading system, and 90%, 95% and 100%, respectively, based on the Kiupel grading system. Of the cases with discordant results, the pre‐treatment biopsies tended to underestimate the grade of the tumour. Based on these results, we conclude that pre‐treatment biopsies are sufficiently accurate for differentiating low‐grade from high‐grade MCTs, regardless of biopsy technique or tumour location.